1995
DOI: 10.1021/bi00003a005
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Base Damage Products from Guanine, Adenine, and Thymine Induced by Exposure of DNA to Ultraviolet Radiation

Abstract: The formation of monomeric products in DNA upon exposure to UV radiation was investigated. Three novel products were identified in DNA in aqueous solution upon exposure to UV radiation at 254 nm in a dose range from 100 to 10,000 J/m2. These were 4,6-diamino-5-formamidopyrimidine, 2,6-diamino-4-hydroxy-5-formamidopyrimidine, and 5-hydroxy-5,6-dihydrothymine. These three products are known to be substrates for base excision repair enzymes involved in the reversal of oxidative DNA damage. The dependence of the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 49 publications
5
78
0
Order By: Relevance
“…Moreover, a recent study demonstrated that the exposure of DNA in aqueous solution to UV radiation at relatively low doses caused formation of several monomeric base damage products (40). As seen in Figs.…”
Section: Formation Of Cyclobutane Pyrimidine Dimers and (6-4) Photoprmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, a recent study demonstrated that the exposure of DNA in aqueous solution to UV radiation at relatively low doses caused formation of several monomeric base damage products (40). As seen in Figs.…”
Section: Formation Of Cyclobutane Pyrimidine Dimers and (6-4) Photoprmentioning
confidence: 88%
“…These data have been taken into account upon calculation of dissociation constants (see above). At higher doses there is a continued accumulation of a broad range of lesions including photoproducts, thymine glycols, interstrand cross-links, and monomeric photoproducts (36,40,41). Formation of (6-4) photoproducts upon irradiation of TT oligonucleotide was not detected (see Fig.…”
Section: Formation Of Cyclobutane Pyrimidine Dimers and (6-4) Photoprmentioning
confidence: 97%
“…[37][38][39][40][41][42] Western blot analysis of serine-15 phosphorylated p53 showed that overexpression of CAT downregulated this protein in normal RE. The interaction between UV irradiation and DNA produces a number of oxidative 43,44 and non-oxidative lesions. 1,45,46 Among various types of DNA damage, cyclobutane pyrimidine dimers (CPD) or 6-4 photoproducts are believed to be the major type of damage resulting from UVB exposure.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Briefly, epidermis was separated from dermis, homogenized with a Potter homogenizer in lysis buffer (25 mM HEPES pH 7.4, 150 mM NaCl, Triton X-100 1% v/v) and then incubated at 4 1C for 30 min. After 10 min of centrifugation at 12 000 g, aliquots of the supernatant were stored at À80 1C.…”
Section: Protein Quantification By Western Blottingmentioning
confidence: 99%
“…8,[13][14][15] UVB irradiation produces two types of DNA damage: direct lesions, which are due to the absorption of photons by nucleobases; and indirect damage, which is dependent on the production of reactive oxygen species (ROS: H 2 O 2 , OH, 1 O 2 y.). [16][17][18][19][20] Several studies have shown that keratinocyte exposure to UVB irradiation generates ROS in excessive quantities that quickly overwhelm various antioxidant defense systems including non-enzymatic (a-tocopherol and vitamin C) and enzymatic antioxidants (catalase and superoxide dismutase). [21][22][23][24] UVB-induced ROS production leads to cytotoxicity through proteins, lipids and DNA oxidation both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%